Genome-scale characterisation of symbiotic fitness determinants of Rhizobium leguminosarum using INSeq - Wheatley, R (2018)
Mariner-based insertion sequencing (INSeq) has been used to characterise symbiotic fitness determinants in Rhizobium leguminosarum bv. viciae 3841 (Rlv3841) on a whole genome-scale. An INSeq database has been constructed that defines the mutational phenotypes for 7316 genes (99.7% of the genome) in Rlv3841 across nine in vitro and in planta INSeq conditions, including growth on glucose or succinate at both 21% and 1% O2, growth in the pea rhizosphere, attachment to pea roots and pea nodulation (collaboration). A total of 463 genes were identified to be required for the successful nodulation of pea, and a genetic map was generated identifying the specific stages of symbiosis these genes are required in. There was identification of 55 genes required specifically for growth in the rhizosphere and 101 genes required specifically for root attachment. Analysis of the central carbon metabolism pathways indicated presence of a methylglyoxal pathway in Rlv3841 and suggested that in planta bacteroids might synthesise glycogen for carbon storage via gluconeogenesis of the plant-provided TCA- cycle intermediates. Only one gene, RL2393 (glnB), was found to be uniquely essential for growth under 1% O2 with succinate. RL2393 (glnB) encodes the nitrogen regulatory protein (PII). Mutation of glnB effectively generates a constitutively activated glutamine synthesis response that increases the removal of 2-ketoglutarate from the TCA-cycle to combine with ammonium to form glutamine. This removal of 2-ketoglutarate from the TCA-cycle becomes problematic under low O2, replenishing 2-ketoglutarate requires an additional turn of the TCA-cycle and the generation of NADH, NADPH and FADH2 reductant molecules whose reoxidation is limited by O2-availability. Ammonium assimilation similarly relies on the removal of 2-ketoglutarate. A reoxidation block model was proposed, in which the provision of dicarboxylates under low O2 prevents removal of 2-ketoglutarate from the TCA-cycle and the assimilation of ammonium. This reoxidation block model provides a novel driving force behind ammonium export in symbioses, alongside explaining why legumes always provide TCA-cycle dicarboxylates to fuel N2-fixation in the low O2 environment of the nodules.